New sea anemone (Anthozoa: Actiniaria) from Patagonia: Andvakia manoloi sp. nov - Lauretta, D. (Zootaxa, 2013)
A new species of sea anemone from the intertidal zone of San Matias Gulf is described. Andvakia manoloi sp. nov. is a small and inconspicuous species that differs from other species of the genus in number of tentacles, number of mesenteries at proximal and distal part of the column, column division, muscles, cnidae, size, habit and distribution. Andvakia manoloi sp. nov. is the first species of the genus from South America and the southernmost record of the genus.